Level of Depression among Diabetic Patients with Lower Limb Amputation in Lahore, Punjab, Pakistan - Zahra, Tahseen; Ghani, Mansoor; Kausar, Samina; Kausar, Rukhsana (Biological and Clinical Sciences Research Journal, 2025)
Lower limb amputation is a major complication of diabetes mellitus (DM) with profound physical, psychological, and social consequences. Depression is among the most common psychological reactions to amputation, yet it is often underrecognized in diabetic patients, particularly in low-resource settings like Pakistan. Objective: To assess the prevalence and severity of depression and its association with demographic and clinical factors among diabetic patients with lower limb amputation in Lahore, Pakistan. Methods: A cross-sectional descriptive study was conducted in three tertiary care hospitals of Lahore, enrolling 202 adult diabetic patients (above or below knee amputation) with a post-amputation duration of 4 months to 2 years. Patients with prior psychiatric illness or receiving rehabilitation services were excluded. Data were collected using a structured questionnaire capturing demographic and clinical details and a validated depression scale for amputees. Depression scores were categorized as mild (25–50%), moderate (50–75%), and severe (75–100%). Data were analyzed using SPSS v20, with chi-square tests to assess associations (p < 0.05 considered significant). Results: The mean age was 48.3 ± 6.9 years, with 66.3% males and 81.7% having below knee amputations. The mean depression score was 70.50 ± 12.82. Overall, 27.7% had mild depression, 65.3% moderate, and 6.9% severe depression. Depression severity was significantly associated with age (p = 0.023), gender (p < 0.001), education (p < 0.001), occupation (p < 0.001), duration of disability (p < 0.001), and level of amputation (p = 0.039). Notably, 73% reported always feeling “heartbroken in loneliness,” and 30% reported they “always forgot to smile.” Conclusion: Depression is highly prevalent among diabetic patients with lower limb amputation, with the majority experiencing moderate symptoms. Targeted mental health interventions, integrated into post-amputation care, are urgently needed to improve quality of life and rehabilitation outcomes in this population.